2015
DOI: 10.1051/parasite/2015010
|View full text |Cite
|
Sign up to set email alerts
|

An update onAcanthamoebakeratitis: diagnosis, pathogenesis and treatment

Abstract: Free-living amoebae of the genus Acanthamoeba are causal agents of a severe sight-threatening infection of the cornea known as Acanthamoeba keratitis. Moreover, the number of reported cases worldwide is increasing year after year, mostly in contact lens wearers, although cases have also been reported in non-contact lens wearers. Interestingly, Acanthamoeba keratitis has remained significant, despite our advances in antimicrobial chemotherapy and supportive care. In part, this is due to an incomplete understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
696
0
57

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 577 publications
(758 citation statements)
references
References 109 publications
(157 reference statements)
5
696
0
57
Order By: Relevance
“…Contact lens related keratitis is the major risk factor in patients needing corneal transplantation [21]. Variety of contact lens markets, environmental issues like water storage and disinfection are known to aggravate the contact lens infection [22]. Also, inappropriate lens wear and absence of awareness of lens usage and care are some other risk factors for corneal ulcer among contact lens wearers [23].…”
Section: Discussionmentioning
confidence: 99%
“…Contact lens related keratitis is the major risk factor in patients needing corneal transplantation [21]. Variety of contact lens markets, environmental issues like water storage and disinfection are known to aggravate the contact lens infection [22]. Also, inappropriate lens wear and absence of awareness of lens usage and care are some other risk factors for corneal ulcer among contact lens wearers [23].…”
Section: Discussionmentioning
confidence: 99%
“…The Schirmer test strips were seeded less than 24 h after collection onto 2% nonnutrient agar (NNA) plates with a layer of heat-inactivated Escherichia coli at 28 uC and were monitored daily for the presence of free-living amoebae as previously described (Lorenzo- Morales et al, 2005Morales et al, , 2015. The isolates were cultured axenically in 75 cm 2 culture tissue flasks without shaking, at 28 uC, in PYG medium [0.75% (w/v) proteose peptone, 0.75% (w/v) yeast extract, and 1.5% glucose] supplemented with 20 mg ml 21 gentamicin.…”
Section: Methodsmentioning
confidence: 99%
“…Attempts to correlate pathogenicity with certain genotypes continue to be made although it has been shown that 90% of Acanthamoeba isolates that produce infections belong to the T4 genotype, suggesting that the abundance of T4 isolates in human infections is most likely due to their greater virulence and/or other properties that enhance their transmissibility, as well as to their decreased susceptibility to chemotherapeutic agents (Khan, 2006;Lorenzo-Morales et al, 2013, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to low hygiene standards and water quality with a greater risk of infection in poor countries. In addition, the widespread use of contact lenses and associated complications in wealthier countries contributes to severe keratitis (2,3). Staphylococcus aureus and Pseudomonas aeruginosa are two predominant gram-positive and gram-negative bacterial strains responsible for causing this disease (1,4,5).…”
Section: Introductionmentioning
confidence: 99%